Understanding Destination Image of Eka Karya Botanical Garden, Bali: A Tourist Perspective: . - Anak Agung Ayu Ribeka Martha Purwahita; Jesihando R. Tulung; Ni Putu Rika Sukmadewi; I Made Weda Satia Negara (Yayasan Literasi Sains Indonesia, 2025)
This study investigates the destination image of Eka Karya Botanical Garden Bali by analyzing tourists’ perceptions through cognitive, affective, and conative dimensions. Employing a descriptive qualitative approach, data were collected from domestic and international visitors using in-depth interviews, participant observations, and documentation of both official sources and online reviews. The findings reveal that, in the cognitive dimension, tourists highly value the uniqueness of the tropical plant collections, the cool mountain climate, and the educational facilities, although shortcomings in infrastructure and supporting facilities such as shuttle buses, signage, and toilets were noted. In the affective dimension, the majority of tourists associated the garden with positive feelings of peace, refreshment, and relaxation, while external factors such as overcrowding and unfavorable weather occasionally disrupted the experience. In the conative dimension, domestic tourists expressed a high intention to revisit, particularly for family recreation and educational purposes, whereas international tourists tended to regard one visit as sufficient. However, their strong willingness to recommend the destination through word-of-mouth and online platforms indicates significant indirect promotional value. Overall, this research highlights that the destination image of Eka Karya Botanical Garden Bali is shaped not only by its cognitive attributes but also by its emotional appeal and its ability to stimulate behavioral responses. These findings provide both theoretical contributions to destination image studies and practical insights for destination managers in enhancing the competitiveness of nature-based and educational tourism destinations in Indonesia.